The effect of financial literacy and financial capability on the interest in social investment-based cash waqf linked Sukuk investment - Pinasti, Ulfi Sheila; Achiria, Siti (Universitas Islam Indonesia, 2024)
IntroductionThe Cash Waqf Linked Sukuk (CWLS) represents an innovative instrument that combines Islamic philanthropy and investment principles to support social development. Despite its potential, Generation Z's participation in CWLS remains limited, presenting a challenge for its broader adoption.ObjectivesThis study examines the influence of financial literacy and financial capability on Generation Z's interest in CWLS investments. It seeks to identify the key barriers and enablers shaping investment behavior in the context of Islamic social finance.MethodUsing a quantitative approach, data were collected from 100 Generation Z respondents in Yogyakarta through structured questionnaires. Multiple regression analysis was employed to assess the relationship between financial literacy, financial capability, and investment interest in CWLS.ResultsThe findings indicate that financial literacy and financial capability have significant positive effects on investment interest in CWLS. Respondents with higher financial literacy demonstrated greater awareness of CWLS benefits, while stronger financial capability enabled practical decision-making. However, issues of trust in waqf management and limited awareness of CWLS were identified as barriers to participation.ImplicationsThe results underscore the importance of targeted financial education, transparency in waqf management, and innovative outreach strategies to enhance CWLS adoption. These insights are critical for policymakers, educators, and financial institutions in promoting Islamic social finance.Originality/NoveltyThis study contributes to the growing body of knowledge on Islamic social finance by exploring the unique dynamics of Generation Z's engagement with CWLS. It highlights actionable strategies to address barriers and foster greater participation in waqf-based investments.